Cytological evidences of the role of Meta-topolin and Benzyladenin in barley root tips - Huyluoğlu, Zekiye; Ünal, Meral; Palavan-Ünsal, Narçin (İstanbul Kültür Üniversitesi, 2008)
The responses of mitotic activity affecting root growth to benzyladenine (BA) and meta-topolin (mT) which is thought to be alternative of BA were studied with time and dose dependent experiments in Hordeum vulgare Tarm-92. The all concentrations of mT caused an induction on mitotic index. 10-5 mT was the most effective stimulator, increasing division frequency from 16 to 26 BA treatment exhibited variations; the low concentrations (10-5 M and 10-6 M) increased the mitotic index but the higher concentration (10-4 M) decreased. The values of mitotic index reflected to the elongation of roots, coordinately. BA and mT are both affected chromosomal behavior and caused abnormalities such as unoriented metaphase, chromosome bridges, 2 nucleate cells, micronuclei formation.
Keywords: meta-topolin; Cytological; nucleate cells; sitolojik; hücreleri çekirdekleştirmek